Business models and foreign operation modes of digital service providers - Ojala Arto; Paavilainen-Mäntymäki Eriikka (Routledge, 2025)
Digital service providers apply different business models based on the characteristics of a firm’s service offering and its business logic. Even selling of digital services over the Internet is not a problem as such; these firms are often struggling with the problem of how to find potential foreign customers for their innovative services and how to serve customers that are located around the globe. While the extant literature offers some insights about the role of the firm’s business model in a foreign operation mode choice, the relationship between a business and a selected foreign operation mode is far from clear. Using an in-depth, qualitative, multi-case study, this study attempts to understand this connection better. The findings of this study reveal that while digital service providers used rather similar foreign operation modes, the roles and tasks of the foreign operation modes varied considerably based on the service and business model applied. That is, the applied business model is clearly related to the firm’s foreign operation mode, driving what types of activities distributors and subsidiaries are able to undertake in foreign markets.
Sustainable International Business Models in a Digitally Transforming World